110k views
1 vote
What’s the correct answer

What’s the correct answer-example-1

1 Answer

4 votes


A=\left[\begin{array}{ccc}-1\\4\\4\end{array}\right] \\\\F=\left[\begin{array}{ccc}0&-2\end{array}\right] \\\\A\cdot F=\left[\begin{array}{ccc}-1\\4\\4\end{array}\right] \cdot\left[\begin{array}{ccc}0&-2\end{array}\right] =\left[\begin{array}{ccc}(-1)(0)&(-1)(-2)\\(4)(0)&(4)(-2)\\(4)(0)&(4)(-2)\end{array}\right]\\\\=\left[\begin{array}{ccc}0&2\\0&-8\\0&-8\end{array}\right]

User Letin
by
6.1k points